Dominance of Spouses of Igbo Households in Purchase Decision of Household Goods in Anambra State, Nigeria - Okwuchukwu Marcus, Anyasor (British Journal of Marketing Studies, 2019)
The objective of the study was to determine the extent of influence of couples in the purchase decision of selected household products/services - children schooling, sitting room sofa, television, refrigerator, car/motor-cycle and land property, for the family. 200 couples were sampled. Data were analyzed in measures of central tendency, and t-tests statistics which results indicated: (1) in need recognition stage of household purchase decision, sitting room sofa, television, car/motorcycle and land property are significantly husband-dominant; refrigerator is significantly wife-dominant; children-schooling is not statistically significant joint decision; (2) in information search stage, children-schooling and sitting room sofa are significantly low influence joint decision; television, car/motorcycle and land property are significantly husband dominant; refrigerator is low influence joint decision and not significant and; (3) in the final decision stage, children-schooling, sitting room sofa, television, car/motorcycle and land property are significantly husband-dominant. Given that decision for almost all the products was husband-dominant, Anambra State of Nigeria was concluded a patriarchal – husband-dominant society. Therefore, marketers of major household goods/services in the area should direct their marketing campaigns majorly at the husbands.